Due frontiere della filosofia educativa oggi: il compito plurale e il modello più critico - Cambi, Franco (Studi sulla Formazione/Open Journal of Education, 2025)
Leading aim of this paper is to try to establish the current profile of the philosophy of education and its critical identity, which must be kept alive in addressing various pedagogical problems, as well as its more organic and complex model of philosophy, critically defined and shared today. These two perspectives are different (one systematic, the other rigorous), but they must work closely together in the current era, more paedagogico. Thus, pedagogy, as a high and noble knowledge, bearer of the possible and democratic developments of the historical future, to which the "principle of hope" is today assigned, must rethink itself in the light of metacriticism to offer itself to both personal and social thought and action as a Great Rule to be placed at the center of human action and brought to its Full Flowering, perhaps inaugurating a new path of Civilization.